Diagnostic Survey of Biological Measurements Used to Determine Bone Mineralization in Pigs Across the US Swine Industry - Hadley R. Williams; Mike D. Tokach; Jason C. Woodworth; Joel M. DeRouchey; Robert D. Goodband; Jon R. Bergstrom; Michael C. Rahe; Christopher L. Siepker; Panchan Sitticharoenchai; Jordan T. Gebhardt (Kansas Agricultural Experiment Station Research Reports, 2023)
Pigs from 64 commercial sites across 14 production systems in the Midwest US were used to evaluate the baseline biological measurements used to determine bone mineralization. Three pigs were selected from each commercial site representing: 1) a clinically normal pig (healthy); 2) a pig with evidence of clinical lameness (lame); and 3) a pig from a hospital pen that is assumed to have recent low feed intake (unhealthy). Pigs ranged in age from nursery to market weight, with the three pigs sampled from each site representing the same age or phase of production. Blood, urine, metacarpal, fibula, 2nd rib, and 10th rib were collected and analyzed. Serum was analyzed for Ca, P, and 25(OH)D3, and urine was collected and analyzed for Ca, P, and creatinine. Each bone was measured for density, ash (defatted and non-defatted technique), and breaking strength. A bone × pig type interaction (P<0.001) was observed for defatted and non-defatted bone ash, density, and breaking strength. For defatted bone ash, there were no differences (P>0.10) between pig types for the fibulas, 2nd rib, and 10th rib, but metacarpals from healthy pigs had greater (P<0.05) percentage bone ash compared to unhealthy pigs, with the lame pigs intermediate. For non-defatted bone ash, there were no differences (P>0.10) between pig types for metacarpals and fibulas, but unhealthy pigs had greater (P<0.05) non-defatted percentage bone ash for 2nd and 10th ribs compared to healthy pigs, with lame pigs intermediate. Healthy and lame pigs had greater (P<0.05) bone density than unhealthy pigs for metacarpals and fibulas, with no difference (P>0.10) observed for ribs. Healthy pigs had bones with increased breaking strength compared to lame and unhealthy pigs for metacarpals and 10th ribs (P<0.05) with no differences (P>0.05) between pig types for fibula and 2nd rib. Healthy pigs had greater (P<0.05) serum Ca and 25(OH)D3compared to unhealthy pigs, with lame pigs intermediate. Healthy pigs had greater (P>0.05) serum P compared to unhealthy and lame pigs, with no differences (P>0.05) between the unhealthy and lame pigs. Unhealthy pigs excreted more (P<0.05) P and creatinine in the urine compared to healthy pigs, with lame pigs intermediate. In summary, there are differences in serum Ca, P, and vitamin D between healthy, lame, and unhealthy pigs. Differences in bone mineralization between the pig types varied depending on the analytical procedure and bone. There was a considerable range in values within pig type across the 14 production systems sampled.
Keywords: bone mineralization; finishing pig; nursery pig; serum Ca; serum P; vitamin D